Multiple radial fractures connecting horizontal boreholes – a lab study on the feasibility of the multifrac concept for geothermal heat extraction from deep reservoirs with low permeability. Issue 1 (August 2021) - Stoeckhert, F; Solibida, C; Witte, L; Alber, M
Abstract: We conducted a number of experiments on cubic rock specimens with low matrix permeability to create and investigate multifrac systems for geothermal heat production on laboratory scale. Special focus was set on phenomena impeding the parallel propagation of multiple fractures like stress shadow and redistribution effects, rock heterogeneity and discontinuities. We subjected the specimens to a true-triaxial stress state using servo-controlled hydraulic pistons for external loading. High viscosity fluids were injected into parallel boreholes at controlled volume rates with metering pumps. Pressure transducers were connected to all boreholes to register injection pressure and pressure responses in neighbouring boreholes. We also recorded acoustic emissions during the experiment for spatial and temporal monitoring of fracture growth processes and the interaction between propagating fractures. After the creation of the hydraulic fractures, the hydraulic connection between the boreholes was tested by fluid circulation. As inferred from acoustic monitoring, radial fractures were propagated stable and technically controllable. Hydraulic connection between the boreholes was established and verified by hydraulic circulation.